EVALUASI KINERJA GURU BERSERTIFIKASI - Andhika Imam Kartomo; Slameto Slameto (Kelola: Jurnal Manajemen Pendidikan, 2016)
The study aimed to evaluate certified teachers performance in Temanggung regency district of Gugus Mangga. This study was evalitative research using qualitative dessciptive approach. Subject of this research are teachers, principals and supervisors. Data were collected through interview, observation and documentation. The results of the study showed that performance of certified teachers in planning aspect of learning and evaluation is in good category. While the performance of certified teachers in presentation and capacity building is in the less than good category. The recommendation given for teachers in preparing lesson plan (RPP) should included aspect of communication and information technologies and also followed by the development of activities. Recommendation for schools is organizing textbooks procurement so that students can have a good process of learning. Recommendation for regional government is to provide assistance of textbooks procurement for schools which has not enough textbook. Besides that the education office recommended to make self-development program for teachers in order to develop and improve the quality of education.